Science and Religion: Reason and Faith - Rockmore, Tom (Journal of Dharma, 1983)
The problem of the relation of science and religion is as important as it is complex, so as to make it difficult to approach more than a single aspect of this relation in a short paper. I have chosen here to concentrate on the relation in question in terms of the distinction between reason and faith, surely a significant aspect of the problem, although not necessarily the only one, yet peculiarly important since it is the central distinction in terms of which members of the modern philosophic tradition have tended to understand both the difference between science and religion as well as their own relation to both spheres. The point I wish to make is that viewed from the perspective of the modern philosophic tradition the attempt to make out an absolute distinction between reason and faith has not been successful, and that in consequence the philosophic grasp of its own relation to science requires further thought.